Reliable communication system for 3D vehicles using heterogeneous networks - Cardiga, Filipe Miguel Ferreira (2017)
Today UAV’s are used in multiple applications, from military to the simplest commercial drones. Generally in order to control these devices, RF signals are used and one of the limitations on currently used RF to control, transfer telemetry or even video streaming is the line of sight. In order to surpass this limitation, several works on using mobile networks were deployed successfully. The focus of this thesis is on the exploration of the redundancy, the throughput increase and even eventually some communications cost reduction provided by using multiple links and provide scalable intelligent algorithms that could deliver the intended results. Another interesting addition will be the use of open source software in order to avoid the costs and other limitations inherent to proprietary software.